2022
DOI: 10.1002/jcp.30735
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of melatonin on liver fibrosis: A systematic review of current biological evidence

Abstract: Hepatic fibrosis is a reversible response to either acute or chronic cellular injury from a wide variety of etiologies, characterized by excessive deposition of extracellular matrix resulting in liver dysfunction and cirrhosis. Melatonin (N‐acetyl‐5‐methoxytryptamine), the main product secreted by the pineal gland, is a multitasking indolamine with important physiological functions such as anti‐inflammatory and antioxidant actions, modulation of circadian rhythms, and immune system enhancement. Among the numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…However, melatonin and cisplatin-cotreated rats exhibited a marked decrease in ovarian TGF-β1 expression and collagen deposition in ovarian tissue. These findings agreed with different studies that reported melatonin administration either intraperitoneally, intravenously, orally, or in drinking water was able to reduce TGF-β expression and decrease tissue and organ fibrosis [49]. Melatonin exerts anti-fibrosis effects by inhibition of epithelial cell injury, including apoptotic and necrotic changes, inflammatory cell infiltration, and the expression of fibrosis-inducing factors, in particular, TGF-β.…”
Section: Discussionsupporting
confidence: 92%
“…However, melatonin and cisplatin-cotreated rats exhibited a marked decrease in ovarian TGF-β1 expression and collagen deposition in ovarian tissue. These findings agreed with different studies that reported melatonin administration either intraperitoneally, intravenously, orally, or in drinking water was able to reduce TGF-β expression and decrease tissue and organ fibrosis [49]. Melatonin exerts anti-fibrosis effects by inhibition of epithelial cell injury, including apoptotic and necrotic changes, inflammatory cell infiltration, and the expression of fibrosis-inducing factors, in particular, TGF-β.…”
Section: Discussionsupporting
confidence: 92%
“…San-Miguel, B. et al collated studies over the past 10 years on the anti-fibrotic effects of melatonin and discuss the cellular and molecular mechanisms that prevent progression of liver fibrosis, cirrhosis, and liver cancer [ 79 ]. Two studies using human HSCs cells LX-2 and the primary isolated HSCs showed that the expression levels for liver fibrosis markers (α-SMA, type 1 collagen and TGF-β) decreased after melatonin treatment [ 80 , 81 ].…”
Section: Autophagy In Mafldmentioning
confidence: 99%
“…Two studies using human HSCs cells LX-2 and the primary isolated HSCs showed that the expression levels for liver fibrosis markers (α-SMA, type 1 collagen and TGF-β) decreased after melatonin treatment [ 80 , 81 ]. Several animal studies showed that melatonin decreased the expression levels for liver fibrosis markers TGF-β, MMP9, and TIMP1 [ 79 ]. Of the three studies discussing the regulation of autophagy by melatonin, two showed a positive effect and one showed a negative effect on autophagy activity [ 79 ].…”
Section: Autophagy In Mafldmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 69 ]. Tahan, Akin [ 70 ] found that bile-duct ligation caused levels of collagen, MDA, luminal, and lucigenin to rise while GSH levels fell; however, melatonin had the opposite effect.…”
Section: Introductionmentioning
confidence: 99%